Empirical Analysis of the Commercial Loan Classification Decision. - Dietrich, J. Richard; Kaplan, Robert S. (The Accounting Review, 1982)
ABSTRACT: The risk classification of commercial bank loans is performed by loan officers, bank controllers, auditors, and bank examiners. Despite the importance of this classification decision, little empirical research has been performed to explain this subjective evaluation procedure. In this paper, a simple linear model is developed which reproduces most of the lending officer's classification decisions. Two variables, a debt-to-total-assets ratio and a funds-flow-to-fixed-commitments ratio, provided most of the explanatory power, but a sales trend variable was also significant. For some of the loans for which the model and the actual classification differed, the model's classification was found to be an advance indicator of a subsequent reclassification by the lending officer. The simple three-variable linear model provided much better predictions of loan risk classification than did two popular bankruptcy prediction models.